2012
DOI: 10.7150/ijbs.5273
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies: The Blockade of Inhibitory Signals

Abstract: T lymphocytes require signaling by the T cell receptor and by nonclonotypic cosignaling receptors. The costimulatory and inhibitory signals profoundly influence the course of immune responses by amplifying or reducing the transcriptional effects of T cell receptor triggering. The inhibitory receptors such as CTLA-4, PD-1, and BTLA have recently drawn much attention as potential targets for immunotherapies. This review focuses on the progress that has been made with the mentioned receptors in the field of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 98 publications
0
18
0
2
Order By: Relevance
“…37,38). Similar results may be obtained when radiotherapy is combined with blockade of other coinhibitory molecules, such as Tim-3, PD-1, or BTLA (39)(40)(41). A recent study has shown that anti-PD-1 antibody produced objective responses, 1 in 4 to 1 in 5 patients with advanced nonsmall cell lung cancer, melanoma, or renal-cell cancer (42).…”
Section: Discussionmentioning
confidence: 59%
“…37,38). Similar results may be obtained when radiotherapy is combined with blockade of other coinhibitory molecules, such as Tim-3, PD-1, or BTLA (39)(40)(41). A recent study has shown that anti-PD-1 antibody produced objective responses, 1 in 4 to 1 in 5 patients with advanced nonsmall cell lung cancer, melanoma, or renal-cell cancer (42).…”
Section: Discussionmentioning
confidence: 59%
“…Several monoclonal antibodies (mAbs) that block these proteins were developed to Ivyspring International Publisher down-regulate the inhibitory immune response, and promote the cellular cytotoxicity of T cells that eliminate tumor cells [6]. Among the immune checkpoint-blocking drugs, the inhibitors targeting PD-1 or CTLA4 were successfully used for treating patients with metastatic melanoma, with improved responses and prolonged survival [7]. This success led to the development of such agents for treating a wide range of malignancies, including renal cell carcinoma (RCC) [8], NSCLC [9][10][11], and acute myeloid leukemia (AML) [12], which further enhanced the response rate compared to conventional treatments, and prolonged the survival time of patients.…”
Section: B7 Familymentioning
confidence: 99%
“…PD-1 występuje na limfocytach cytotoksycznych, ligand dla PD-1-PD-L1 występuje w nadmiarze na komórkach guza. Interakcja PD-1 z PD-L1 ma silną funkcję immunosupresyjną poprzez hamowanie wydzielania cytokin oraz supresję aktywności cytolitycznej limfocytów [86,87]. W badaniach klinicznych wykazano skuteczność humanizowanych przeciwciał monoklonalnych, który funkcja polega na hamowaniu połączenia receptora PD-1 z ligandem.…”
Section: Implikacje Terapeutyczne -Metody Immunoterapii W Raku Płucaunclassified